Literaturas afro-brasileira e africanas: o desafio nos livros didáticos de língua portuguesa para o ensino médio - Costa, Nelzir Martins (Universidade Federal do Tocantins, 2016)
The objective of the research was to analyse how the Law 10.639/2003 is being applied in the textbooks Portuguese language for secondary school, distributed by the National Textbook Program (PNLD). The analysis focused on the observation of the insertion of African-Brazilian and African literatures across the syllabus, aiming to verify a wide scope of materials, were analysed textbooks used in High Schools in the four largest cities that host the Regional Training Directors and Management of the State of Tocantins: Palmas, Araguaína, Porto Nacional and Gurupi. This study required a revival: in the formation of Brazilian society, as well as ethnic-racial relations that permeate this diversity; the systematic education and the laws governing it, checking the guidelines for working with ethnical and racial issues and proposed education aimed at equal rights, besides the approach of literature as a necessary element of human education, considering the importance of the production of African – Brazilian and African literatures for the affirmation of black identity and as a symbol of the independence from European standards in the Portuguese – speaking African countries. What we found is that, despite the expiracion of 10 (ten) years from the approval of Law 10.639/2003 , the Portuguese Language textbooks for high schools still find it difficult to present such content. Denoting that its approach is presented in a superficial and restricted form in most collections analysed. Which requires considerations by area teachers, authores, publishers, and Ministry of Education trough PNLD.